Multiple intravenous antibiotics usage is associated with intravenous immunoglobulin resistance in Kawasaki disease - Zon-Min Lee; Chiao-Lun Chu; Chi-Hsiang Chu; Ling-Sai Chang; Ho-Chang Kuo (Elsevier, 2022)
Background: Kawasaki disease (KD) is a form of systemic vasculitis that primarily affects children under the age of 5 years old. Antibiotics are often prescribed for KD patients even before a diagnosis is made due to their prolonged fever and elevated inflammatory markers. Therefore, the purpose of this study was to investigate the impact of antibiotics usage on the disease outcome of KD. Methods: We carried out a retrospective chart review of children between 2005 and 2017 for initial immunoglobulin (IVIG) treatment of KD. KD children with initial IVIG treatment more than 10 days after the onset of symptoms were excluded. Results: In total, 280 children were eligible for this study, among which 209 had been treated with antibiotic(s) and 71 had not been. The IVIG resistance rates were 5.6% (4/71), 8.9% (10/112), and 21.6% (21/97) in non-users, single-drug users, and multiple-drug users, respectively (r = 0.205, p = 0.003). The IVIG resistance rate of the multiple antibiotics drug users in KD patients was significantly higher than the other two groups. Furthermore, the likelihood of IVIG resistance was found to increase with elevated C-reactive protein (CRP) values (1.010/unit, p < 0.001) but not with total white blood cell (WBC) count (p = 0.466). Conclusion: The probability of IVIG resistance increases with elevated CRP values and the use of multiple IV antibiotics, thus indicating that physicians should be prudent in administering multiple IV antibiotics when treating assumed infections in KD children.